Proses Berpikir Divergen Anak Usia 5-6 Tahun dalam Permainan Konstruktif Bombik Tazoz - Nur Mufida; Ardhana Reswari (Universitas Islam Lamongan, 2026)
The low level of divergent thinking stimulation in preschool children through meaningful play activities, especially constructive play, is an important issue in the development of creativity and problem-solving skills in early childhood. This study aims to describe the divergent thinking process of 5-6-year-old children in constructive play with bombik tazoz and identify the factors that influence it at RA Nurul Huda Pamekasan. The study used a descriptive qualitative approach with 23 subjects aged 5-6 years old. Data collection techniques included observation, interviews, and documentation, while data analysis used the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The results showed that bombik tazoz play stimulated children's divergent thinking through four main aspects: fluency in generating various ideas, flexibility in changing construction forms, originality in creating unique works, and elaboration in developing and explaining the results of their work. The divergent thinking process is influenced by internal factors such as self-confidence, motivation, and enthusiasm, as well as external factors including a conducive play environment, social interaction with peers, and the role of teachers who provide freedom of expression without pressure. Children demonstrate the ability to explore various possible solutions and produce diverse construction products. Constructive bombik tazoz games are effective as a learning medium for developing the divergent thinking abilities of 5-6 year old children, with the support of a conducive play environment and the optimal role of the teacher as a facilitator.